Characteristics of several soybean varieties (Glycine max L.) and weed management systems in an effort to increase productivity in low land rice - Fattah, Abdul; Negara, Abdi; Supriadi, Khojin; Hannan, Muhammad Fitrah Irawan; Ardjanhar, Asni; Beding, Petrus A.; Najamuddin, Erwin; Pustika, Arlyna Budi; Susilawati, Susilawati; Nonci, Nurnina; Latifah, Evy; Arifin, Zainal; et al. (Frontiers in Sustainable Food Systems, 2024)
Soybean productivity in paddy fields is influenced by variety selection and grass management practices. This study aimed to assess several soybean varieties and evaluate the impact of soil processing and weed control on Summed Dominance Ratio (SDR), as well as growth and yield of soybean seeds. Conducted in Sungai Kakap, Kubu Raya, West Kalimantan, during 2021, the research employed a Randomized Block Design with 15 treatments and 3 replications.Treatments included various combinations of tillage methods, weed control techniques, and mulching. The study identified four soybean varieties Detap-1, Derap-1, Devon-1, and Dena-2 with large seed sizes and high yields. These varieties also exhibited resistance to common pests such as Etiella zinkenella, Riptortus linearis, and Spodoptera litura. Weed composition analysis revealed O. sativa and Ageratum conyzoides as dominant species. Weed dry weight was lowest in the perfect tillage + pre-emergence herbicide treatment and highest in the minimum tillage + weeds are not controlled treatment. The highest plant growth and seed yield were observed in the minimum tillage + pre-emergence herbicide and perfect tillage + preemergence herbicide treatments. Plant height, number of pods per plant, number of seeds per plant, and dry seed yield were significantly higher in these treatments compared to others. In conclusion, varieties Detap-1, Derap-1, Devon-1, and Dena-2 possess suitable physical characteristics for cultivation in Indonesia. The most effective grass management models identified were minimum tillage + pre-emergence herbicide and perfect tillage + preemergence herbicide. These findings contribute to optimizing soybean cultivation practices, emphasizing varietal selection and weed control strategies for improved crop performance.